1999
DOI: 10.1128/jb.181.3.748-756.1999
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing in Burkholderia cepacia : Identification of the LuxRI Homologs CepRI

Abstract: Burkholderia cepacia has emerged as an important pathogen in patients with cystic fibrosis. Many gram-negative pathogens regulate the production of extracellular virulence factors by a cell density-dependent mechanism termed quorum sensing, which involves production of diffusible N-acylated homoserine lactone signal molecules, called autoinducers. Transposon insertion mutants of B. cepacia K56-2 which hyperproduced siderophores on chrome azurol S agar were identified. One mutant, K56-R2, contained an insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
140
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(149 citation statements)
references
References 71 publications
8
140
0
1
Order By: Relevance
“…We also analyzed the AHL pro¢les of the two cocolonizing B. cepacia strains. In agreement with the results of Lewenza et al [19] it was found that the B. cepacia strain isolated from patient P1 produced an AHL molecule that, based on TLC analyses, most likely represents OHL. In addition, signi¢cant amounts of a second AHL molecule, the mobility of which was found to be similar to that of HHL, were detected (data not shown).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We also analyzed the AHL pro¢les of the two cocolonizing B. cepacia strains. In agreement with the results of Lewenza et al [19] it was found that the B. cepacia strain isolated from patient P1 produced an AHL molecule that, based on TLC analyses, most likely represents OHL. In addition, signi¢cant amounts of a second AHL molecule, the mobility of which was found to be similar to that of HHL, were detected (data not shown).…”
Section: Resultssupporting
confidence: 91%
“…cepacia syndrome', a fulminant, fatal pneumonia [2]. Recently, B. cepacia has been demonstrated to utilize a N-octanoyl-L-homoserine lactone (OHL)-dependent quorum sensing system to control expression of virulence factors [19]. Moreover, it has been shown that spent culture supernatants of P. aeruginosa enhance AHL-regulated virulence factor production in B. cepacia [20].…”
Section: Resultsmentioning
confidence: 99%
“…although in that instance inactivation of a hsR homolog, cepR. actually increased siderophore production [23].…”
Section: Commentsmentioning
confidence: 98%
“…Expression of bacterial functions important for hostcolonization and pathogenicity is commonly cell-densitydependent and related to the accumulation of N-acyl homoserine lactones (AHLs) [10,11]. Typically such`quorum sensing' systems involve luxI and luxR homologs specifying an AHL synthase and AHL-binding transcriptional activator [10^12].…”
Section: Introductionmentioning
confidence: 99%